2012
DOI: 10.1007/s00418-012-0928-1
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1-positive cells in the subodontoblastic layer possess high potential to differentiate into hard tissue-forming cells

Abstract: The cells of the subodontoblastic cell-rich layer in dental pulp are speculated to contain odontoblast progenitor cells because of their positional relationship with odontoblasts as well as their high alkaline phosphatase (ALP) activity. However, it has yet to be determined whether these cells have the ability to differentiate into odontoblastic cells. In the present study, we firstly found that the majority of cells in the subodontoblastic layer expressed Thy-1, a cell-surface marker of stem and progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
4
31
1
Order By: Relevance
“…Similarly, periosteal cells sorted based on Thy1 expression showed higher proliferative capacity and osteogenic potential in vitro and in vivo compared with unsorted periosteum‐derived cell populations (30). Similarly, subodontoblastic dental pulp stem cells expressing higher Thy1 levels on the cell surface showed accelerated induction of alkaline phosphatase activity and mineralized matrix formation and a higher capacity to form hard tissue compared to the cells with lower expression of Thy1 (31). Taken together, these findings coupled with the reports outlined above, establish Thy1 as a positive regulator of OB differentiation that is centrally involved in bone homeostasis, especially in the context of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, periosteal cells sorted based on Thy1 expression showed higher proliferative capacity and osteogenic potential in vitro and in vivo compared with unsorted periosteum‐derived cell populations (30). Similarly, subodontoblastic dental pulp stem cells expressing higher Thy1 levels on the cell surface showed accelerated induction of alkaline phosphatase activity and mineralized matrix formation and a higher capacity to form hard tissue compared to the cells with lower expression of Thy1 (31). Taken together, these findings coupled with the reports outlined above, establish Thy1 as a positive regulator of OB differentiation that is centrally involved in bone homeostasis, especially in the context of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…One day after preparation, the immunoreactivity of CD90 disappeared just under the cavity area (b). Previous studies demonstrated that CD90-highly immunoreactive cells had the ability to differentiate into odontoblasts (18,27). After 5 days, CD90-immunoreactive cells localised at the subodontoblastic layer again (d).…”
Section: Differentiation After Cavity Preparation and Its Relationshmentioning
confidence: 93%
“…In the control group, CD90-immunoreactive cells were mainly observed at the subodontoblastic layer of coronal pulp (a). stem cell marker in normal dental pulp (18,27). After 3 days, CD90immunoreactive cells were not present, whereas the rearrangement of cells indicating odontoblasts was detected in contact with the dentine (c).…”
Section: Differentiation After Cavity Preparation and Its Relationshmentioning
confidence: 99%
“…These stem cells are found at the periphery of blood vessels in the central region of the pulp and have multilineage potential (Iohara et al 2008;Karaoz et al 2011). In fact, earlier we showed that cells in the subodontoblast cell-rich layer have high mineralization ability and form a bone-like matrix after subcutaneous transplantation (Hosoya et al 2012). In addition to these possibilities, the periodontal ligament (PDL) is also thought to be a source of osteoblast-like cells.…”
mentioning
confidence: 99%